2000
DOI: 10.1177/03635465000280042001
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of the Infrapatellar Branches of the Saphenous Nerve to Arthroscopy Portals and Incisions for Anterior Cruciate Ligament Surgery: An Anatomic Study

Abstract: The purposes of this study were 1) to carefully define the anatomic distribution of the infrapatellar branches of the saphenous nerve, 2) to provide the surgeon with reliable parameters for where the nerve is most commonly encountered, and 3) to provide specific surgical recommendations to minimize the risk of nerve injury. To accomplish these goals, we dissected 20 cadaveric, fresh-frozen, matched-pair knees. Calipers were used to measure the distance from the nerve to three clinically relevant and easily rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
97
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(103 citation statements)
references
References 11 publications
4
97
0
2
Order By: Relevance
“…Finding consistency within IPBSN branching has been the aim of many studies since. 2,9,14,16,18,34 Despite our relatively small sample size of 10 cadaveric knees, the relationship between the IPBSN and bony landmarks was no different than those reported in the large seminal study by Mochida and Kikuchi. 24 In their study of 129 knees, these authors reported an insignificant difference in the mean distance from the IPBSN to the midpatella in left (52.2 mm) and right (54.2 mm) knees.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Finding consistency within IPBSN branching has been the aim of many studies since. 2,9,14,16,18,34 Despite our relatively small sample size of 10 cadaveric knees, the relationship between the IPBSN and bony landmarks was no different than those reported in the large seminal study by Mochida and Kikuchi. 24 In their study of 129 knees, these authors reported an insignificant difference in the mean distance from the IPBSN to the midpatella in left (52.2 mm) and right (54.2 mm) knees.…”
Section: Discussionmentioning
confidence: 55%
“…1,8,12,28,33,34 Our clinical study of 109 patients revealed no such complications. Our anatomic study showed that the medial and lateral epicondyles can serve as dependable landmarks for portal placement (± 4.7 mm and ± 3.8 mm, respectively).…”
Section: Discussionmentioning
confidence: 65%
“…1 From the results presented here, division of cutaneous nerve branches is common in the SLA and the PA. Studies have reported better patient outcome following knee arthroscopy and arthroscopic ACL reconstruction when the incision lines are placed horizontally (parallel to the infragenicular branch of the saphenous nerve) rather than vertically, across the path of the nerve. 12 Similarly, symptoms (pain and numbness) after harvesting of bone from the posterior iliac crest are reduced when incisions are made parallel to the nerves, rather than perpendicular to them. 13 There is conflicting evidence for the benefits of MIS in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…All the cadavers used had been embalmed; the position of the hip at rigor mortis may have influenced the position of cutaneous nerves. However, unlike nerves around the knee where joint movement can influence nerve position markedly, 12 the hip position during dissection was similar to the intra-operative position at the time of skin incision for THA. There is also a risk of inter-observer bias as the dissections were performed by two of the authors independently.…”
Section: 21-23mentioning
confidence: 99%
See 1 more Smart Citation